Studying The Activity Of In Vitro Antiseptics Decasan, Furacillin and Chlorhexidine Bigluconate Against Hospital Strains of S. Aureus, E. Coli, Klebsiella Spp., P. Melaninogenica Separated from the Bed of the Soleus Muscle (Texas Journal of Medical Science, 2022)
A prospective analysis of the case histories of 38 DM patients who underwent shin amputation in the Department of Wounds and wound infection at the A.V. Vishnevsky National Research Center for Surgery of the Ministry of Health of the Russian Federation during 2017-2019 was performed. All the studied patients were taken biological material during the operation and the comparative antimicrobial activity of the antiseptics decasan, chlorhexidine bigluconate and furacillin was studied against strains of S. aureus, E. Coli, Klebsiella spp., P. melaninogenica. The analysis of the obtained results revealed that 0.02% decasan solution exhibits high antimicrobial activity in relation to aerobic and anaerobic hospital strains of microorganisms.